2013
DOI: 10.11622/smedj.2013243
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of target-controlled infusion of propofol and remifentanil with high frequency jet ventilation in fibre-optic bronchoscopy

Abstract: O r i g i n a l A r tic le 689 I NTRO D U C TIO NOf all endoscopic procedures, bronchoscopy without sedation might be one of the most painful and uncomfortable experiences. Therefore, unless absolute contraindications exist, sedation or anaesthesia is recommended for patients undergoing bronchoscopy.( Recently, propofol has proven effective during bronchoscopy, achieving similar results as the combined administration of midazolam and opiates in aspects such as sedation, amnesia and patient tolerance. (6) Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Bronchoscopy without sedation is a painful and uncomfortable experience. [ 17 ] TCI anesthesia with propofol and short-acting opioids is reported to provide satisfactory anesthesia for flexible bronchoscopy, when assisted with repeated topical anesthesia every 10 to 15 minutes. [ 18 ] However, cough, apnea, hypoxemia during procedure could not be fully avoided and thus disrupted the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bronchoscopy without sedation is a painful and uncomfortable experience. [ 17 ] TCI anesthesia with propofol and short-acting opioids is reported to provide satisfactory anesthesia for flexible bronchoscopy, when assisted with repeated topical anesthesia every 10 to 15 minutes. [ 18 ] However, cough, apnea, hypoxemia during procedure could not be fully avoided and thus disrupted the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] However, cough, apnea, hypoxemia during procedure could not be fully avoided and thus disrupted the procedure. [ 17 19 , 21 ] Previous study reported that anesthesia for flexible bronchoscopy required TCI via propofol Cp of 3 to 4 μg/ml. [ 17 ] It has also been demonstrated that effect-site C 50 concentration of propofol was 2.2 μg/ml when subjects had no response to verbal stimulation and shaking.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the narrow therapeutic index between moderate sedation and respiratory depression, propofol is now strongly recommended for use only by anesthesiologists with close monitoring. [27,28] Ketamine has been more and more used in the children's flexible bronchoscopy for its sympatholytic and analgesic effects as well as being a potent bronchodilator, but it has the deficiency of increasing salivation and secretions and cannot attenuate the upper airway reflexes. [29,30] Though opioids are frequently used during bronchoscopy for analgesic property, their sedative effect is weak to complete the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…However, its pharmacological effects vary among patients, and it may depress the ventilatory drive and finally cause apnea, especially in patients with co-morbidities who are taking other respiratory depressant drugs [20, 21]. As a short-acting anesthetic agent with rapid recovery, propofol has been widely used in many clinical fields such as gastrointestinal endoscopy, thyroplasty, bronchoscopy, interventional or radiological procedures, and during awake bronchoscopy intubation, for its hypnotic effect [22, 23]. Ketamine, on the other hand, has been increasingly used for flexible bronchoscopy in children for its sympatholytic and analgesic effects, as well as for its potent bronchodilator actions.…”
Section: Discussionmentioning
confidence: 99%